Trends and issues of distance education of adults in Japan - Jubatova, B.N.; Baiseitova, D.S. (KU Publ., 2021)
This paper examines the present situation of the development of distance education in Japan, particularly concerning adults. In Japan, the term “lifelong learning” has become widely used and is central to educational policies that actively address critical subjects occuring in a wide range of education in a rapidly changing society. Japan's higher education system is suffering from a steady decline in the number of high school graduates as a result of declining birth rates. One way to tackle this problem is to attract new demographic groups of students, such as adults and international students. Besides, the growing number of older adults has led to an increased demand for educational programs. On the other hand, there are numerous issues to be addressed in order to promote adult education in Japan. The COVID–19 pandemic revealed problems in the education system, showing serious gaps both in the principles of organizing lifelong learning and in the implementation of educational programs in this aspect. While online distance education is a strategic instrument that Japanese institutions may adopt to achieve a competitive advantage, it is under-represented in comparison to its global counterparts. In this article, the factors that influenced the development of distance education in Japan, as well as the reasons that hindered its spread have been considered. The authors have analyzed the features of adult education within the Japanese lifelong education system. Also, we examined the organizations providing distance education (including online) in Japan and the measures taken by the government to further develop distance education for adults amid the pandemic.
Жапониядағы ересек адамдарды қашықтықтан оқыту үрдісі мен мәселелері
Тенденции и проблемы дистанционного образования взрослых в Японии
Keywords: distance education; Japan; lifelong learning; adult education; COVID–19 pandemic; online learning; distance learning